Hubungan Spiritual Well-Being dengan Hardiness pada Pasien Diabetes Melitus Tipe 2 di Poliklinik RS Tingkat III Baladhika Husada Jember - Nurmaidah, Ruri; Widayati, Nur; Sutawardana, Jon Hafan (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Diabetes Mellitus (DM) influence on psychological and physical condition of the patients. Patients arerequired to maintain self-care and to prevent complication which can cause psychological pressure. Thiskind of pressure may affect hardiness of patients in performing self-care. Hardiness may be influenced byspiritual well being. The aim of this study was to analyse the relationship between spiritual well-being andhardiness in patients with type 2 DM. This research applied correlational design with cross-sectionalapproach. A total of 112 respondents were selected by using consecutive sampling technique. The data werecollected by administering questionnaire of Spiritual Well-Being Scale (SWBS) and Hardiness Scale. Dataanalysis was performed by Spearman-rank correlation test with the significance level of 0.05. The resultsshowed that the median score of spiritual well being was 91 (72-100) while the median value of hardinesswas 104 (84-122). There was a significant positive correlation between spiritual well-being and hardiness (pvalue : 0.001 ; r : 0.303). The higher the spiritual well-being the better the hardiness of patients with type 2DM. This research reveals on the importance of assessing spiritual well-being to enhance hardiness inpatients with type 2 DM.